Outcomes of Systematic Nutritional Assessment and Medical Nutrition Therapy in Pancreatic Cancer. Issue 5 (July 2015) - Vashi, Pankaj; Popiel, Brenten; Lammersfeld, Carolyn; Gupta, Digant
Abstract : Objectives: We investigated the nutritional and survival outcomes of medical nutrition therapy by a registered dietitian, along with support from a dedicated nutrition and metabolic support team in pancreatic cancer patients requiring enteral or parenteral nutrition. Methods: Subjective global assessment (SGA) was used to assess nutritional status in 304 pancreatic cancer patients. Using baseline and last SGA, patients were categorized into 3 groups: improved SGA, deteriorated SGA, and unchanged SGA. Kaplan-Meier and Cox regression were used to calculate survival after controlling for relevant confounders. Results: One-hundred twenty-five (41.1%) patients had their SGA unchanged, 87 (28.6%) patients had "improved SGA, " whereas 92 (30.3%) patients had "deteriorated SGA." On univariate survival analysis, the median survival was 7.8, 11.2, and 12.6 months for deteriorated, unchanged, and improved SGA groups, respectively. On multivariate analysis, change in SGA was independently predictive of survival. Patients with deteriorated SGA had 1.5 times (95% confidence interval, 1.1–2.1) greater risk of mortality compared to those with improved SGA. Conclusions: The majority of pancreatic cancer patients (70%) in our study either maintained or improved their nutritional status during cancer treatment. Improvement in SGA correlated with a significantly decreased risk of mortality independent of sex, previous treatment history, and evidence of biological anticancer activity. Abstract : Supplemental digital content is available in the text.